2020
DOI: 10.21009/ijlecr.062.11
|View full text |Cite
|
Sign up to set email alerts
|

Integrating 21st Century Skills Into Translation Classroom: A Brief Perspective on Its Syllabus

Abstract: This study is motivated by the fact that globalization has arrived. There are demands of skills and competencies that must be possessed by a global citizen in general and by students in particular. The current trend in our world is the issue of 21st century skills. As academicians, we need to be one step further to accommodate this demand. This study aimed to explore the 21st century skills and these skills can be integrated in Translation syllabus. The focus of this study is on the exploration of 21st century… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…On the other hand, the result of this study is contradicting with the study conducted by Sumiati et al (2020) that 21 st century skills are only possible to be integrated in the learning outcomes, the materials, the teaching method, and the assessment and evaluation as this study found that problem-solving skills are possibly integrated in five components of the syllabus including basic information of the course, learning outcomes, course objectives, learning method, and course activities.…”
Section: Syllabus Components Which Integrate Problem-solving Skillscontrasting
confidence: 99%
“…On the other hand, the result of this study is contradicting with the study conducted by Sumiati et al (2020) that 21 st century skills are only possible to be integrated in the learning outcomes, the materials, the teaching method, and the assessment and evaluation as this study found that problem-solving skills are possibly integrated in five components of the syllabus including basic information of the course, learning outcomes, course objectives, learning method, and course activities.…”
Section: Syllabus Components Which Integrate Problem-solving Skillscontrasting
confidence: 99%
“…First, incorporating the 4C elements (critical thinking, collaboration, creativity and communication) into the course syllabus, which includes teaching materials, teaching methods, and assessments. Second, detailing the course competencies related to these elements and incorporating the 4C aspects into these competencies [7]. The way to integrate 21st-century skills into the learning process is by implementing activities that encourage learners to think critically, collaborate, create and communicate effectively in the classroom.…”
Section: St Century Skills and Their Integration Into Teaching Materialsmentioning
confidence: 99%
“…People [1]. In addition, the education system in Indonesia is technology-oriented due to IR 4.0, which involves a learning system [2]. This theory means that German is one of the foreign languages that people are very interested in.…”
Section: Introductionmentioning
confidence: 99%